Role of Epstein-Barr Virus and Human Papillomavirus Coinfection in Cervical Intraepithelial Neoplasia in Chinese Women Living With HIV - Feng, Min; Duan, Rufei; Gao, Yang; Zhang, Han; Qiao, Youlin; Li, Qihan; Zhao, Fanghui (Frontiers in Cellular and Infection Microbiology, 2021)
Given that only a small percentage of human papillomavirus (HPV)-positive women develop cancer, HPV is necessary but insufficient for carcinogenesis. Mucosally transmitted viral cofactors appear to contribute to HPV-related cervical cancer, such as Epstein-Barr virus (EBV), but previous studies have shown inconsistent outcomes. The exact role of EBV in cervical cancer remains unclear, and more studies are needed to determine its involvement. In this study, we describe the prevalence of EBV and HPV coinfection in HIV-positive women and explore how abnormal host immune status induced by viral coinfections modulates epithelial gene expression. We found a significant correlation between EBV-HPV coinfection and the incidence of high-grade cervical intraepithelial neoplasia (CIN2+). RNA sequencing indicated that CIN tissues coinfected with EBV and HPV led to significant changes in the gene expression of epithelial differentiation and development compared to normal tissues with HPV infection alone. In particular, several differentially expressed genes (DEGs) are closely associated with cancer, such as CACNG4, which was confirmed to be upregulated at both the mRNA and protein levels. Therefore, these findings provide a proof-of-concept that EBV may act as a cofactor or mediator in HPV-related cervical cancer. Specific genes or proteins, such as CACNG4, may serve as biomarkers that can risk stratify patients based on pathological changes in the cervix.